ISLAM IN OYO AND ITS DISTRICTS IN THE NINETEENTH CENTURY (1978)
This work describes the history and development of Islam in Oyo and its districts in the nineteenth Century. In short, the work is an attempt to see in what way Islam lad moulded the history of the people of Oyo and its districts in the nineteenth Century, The first chapter describes the beginnings of Islam in the area until the period when the religion became stagnant as a result of the fall of-the Old Oyo Empire, In this way, we are able to see the various difficulties militating against Islam in the area in the early period. In chapter two, we discuss the survival and growth of Islam in the area after the fall of the Old Oyo Empire, The forces, external and internal, responsible for this stage of Islamic growth are discussed in this chapter, Thus we are able to see a clear picture of how Islam surmounted the initial difficulties generated by the decline and fall of the Old Oyo Empire and how it eventually established itself strongly alongside the age-long traditional religion. Chapter three deals with the expansion of Islam during the increasing influx of Christian missionaries into Oyo and its districts. In this chapter, the difficulties facing the missionaries and their effects on the expansion of Christianity and Islam are discussed, Furthermore, the challenge of Christianity and the reaction of the Muslims to the challenge are examined. In this way, we are able to see why Islam became the dominant religion in the area in the nineteenth Century. In chapter four, we examine the status of Islam in the period when the area, known as Oyo and its districts, was brought within the web of Western civilization. In this way, we are able to see the influence of British rule on the expansion and development of Islam in the area in the period between 1894 and 1900. The religio-social significance of Islamic institutions in the area in the nineteenth Century is examined in chapter five. The influence of the institutions on the growth of Islam and how they provided a universal link with the Muslim world are clearly shown in this chapter. The people of Oyo and its districts had been greatly influenced by the traditional religion before the influx of Islam. Thus, in the last chapter, we turn our attention to examining the influence of Islam on the traditional background of the Muslim community. In this way, we are able to see the interaction of the traditional religion and Islam among the people of Oyo and its districts in the nineteenth Century. Since Islam constituted a strong force and became the dominant religion in Oyo and its districts in the nineteenth Century, we conclude by examining the extent of its success among the people of the area in this period.